Managing marital disputes in Lebanese religious courts from a social work perspective: A study on the importance of family mediation offices in Lebanese Druze religious courts as a model - Hakim, Ghada Osmat El; Mansour, Rania Mohamad (Edelweiss Applied Science and Technology, 2024)
This study explores how marital disputes are managed in the Druze community's religious courts from theoretical and practical perspectives and analyzes the methods and mechanisms used to resolve marital conflicts. This study is categorized as a qualitative approach, as it is a descriptive exploratory study that relies on the phenomenological method to explore how marital conflict is managed in the religious courts of the Druze sect for the Monotheist community. This will be done through the study's theoretical framework and by conducting field interviews with the participants, such as social workers, judges, attorneys, and those going through marital problems. Through these interviews, we hope to learn more about their perspectives on handling marital disagreements and their experiences managing them in religious courts and identify alternative methods for resolving these disputes within the courts. The results of this study and recommendations can be utilized to develop a new strategy for managing marital conflict that aligns with needs and considers scientific standards. This study may help intervenors working with couples reevaluate how they handle disagreements.